The Long-Time Behavior of 2D Nonautonomous g-Navier-Stokes Equations with Weak Dampness and Time Delay. (25th July 2022) - Wang, Xiaoxia; Jiang, Jinping
Abstract : In this paper, we discuss the long-time behavior of g -Navier-Stokes equations with weak dampnesss and time delay. The uniformly attracting sets of processes are obtained. On the basis of the method with asymptotic compactness, the existence of the uniform attractor for the equation is proved with the restriction of the forcing term belonging to translational compacted function space.